2020
DOI: 10.21203/rs.3.rs-27821/v4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Physiological and molecular characterization of active fungi in pesticides contaminated soils for degradation of glyphosate

Abstract: Understanding the physiological and molecular characteristics of naturally occurring fungi in glyphosate pesticide-contaminated environment is crucial to managing its contamination. The study was aimed at isolating and characterizing soil fungi for their physiological roles towards glyphosate degradation. Pure cultures of fungi were isolated from soil contaminated with glyphosate at farms in Lagos, Nigeria. The cultures were grown on minimal salt agar media amended with glyphosate. The best isolates exhibiting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Kulikova et al (2020) [169] report that the biodegradation of the herbicide can be carried out both with the formation of AMPA and sarcosine, the latter being the main degradation pathway. For their part, in the study of Njoku et al (2020) [164] fungal strains were identified capable of degrading glyphosate; this study points out that the selected fungi biodegraded the herbicide through GOX pathway due to the presence of the AMPA metabolite, in exception of Aspergillus fumigatus FJAT-31052. Despite these studies, the metabolic processes related to the degradation of glyphosate in fungi have not been fully described.…”
Section: Fungal Degradation Of Glyphosatementioning
confidence: 96%
“…Kulikova et al (2020) [169] report that the biodegradation of the herbicide can be carried out both with the formation of AMPA and sarcosine, the latter being the main degradation pathway. For their part, in the study of Njoku et al (2020) [164] fungal strains were identified capable of degrading glyphosate; this study points out that the selected fungi biodegraded the herbicide through GOX pathway due to the presence of the AMPA metabolite, in exception of Aspergillus fumigatus FJAT-31052. Despite these studies, the metabolic processes related to the degradation of glyphosate in fungi have not been fully described.…”
Section: Fungal Degradation Of Glyphosatementioning
confidence: 96%